The Role of Information and Communication Technology (ICT) in Shaping Global Economic Integration: A Systematic Literature Review - Pardiyawan, Pardiyawan; Ali, Mukti; Aprilliantoni, Aprilliantoni (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study uses a systematic literature review, or SLR, to examine the role of information and communication technology (ICT) in driving global economic integration. This study uses a systematic literature review, or SLR, to examine the role of information and communication technology (ICT) in driving global economic integration. Through the use of bibliometric analysis using the VOSviewer and PRISMA method, the study identifies research trends, collaborative efforts, and theoretical and empirical knowledge found in the literature from 1990 to 2025. This research focuses on systematic literature (Lit Sistematis). The results show that ICT growth and global economic integration have increased significantly since 2005, with the United States, the United Kingdom, and China making the largest contributions. The theoretical implications highlight the need for more holistic concepts and lengthy studies, while the practical implications highlight the importance of adapting ICT strategies to the local context and encouraging international collaboration. This study provides an important guide for ICT development and the integration of the world economy in the digital age.